Research handbook on legal pluralism and EU law - Davies, Gareth, 1970-; Avbelj, Matej (Research handbooks in European law, 2018)
The Research Handbook on Legal Pluralism and EU Law explores the phenomenon of overlapping legal systems within the European Union, the nature of their interactions, and how they deal with the difficult question of the legal hierarchy between them. The contributors reflect on the history, sociology and legal scholarship on constitutional and legal pluralism, and develop this further in the light of the challenges currently facing the EU. Addressing pluralism within policy areas such as EMU, migration, and external relations, and applying different perspectives - from the constitutionalist to the Foucauldian - this diverse collection of thinkers about EU law ask whether a pluralist perspective is part of the problem or part of the solution. Contributors offer both critical and positive assessments of the value of pluralist thinking in the EU whilst addressing major issues facing the EU now - Brexit, populism, migration, the Euro-crisis - and asking what lessons can be learned from and for pluralism. This Research Handbook will be invaluable reading for legal academics specialising in EU law, EU constitutional Law, legal theory and political scientists focused on legal aspects of EU integration. Students on advanced courses in EU law and EU constitutional law, as well as judges at the Court of Justice and higher national courts, will also find this stimulating reading.